KRITIK SOSIAL NOVEL SABAR TANPA BATAS KARYA ADHITYA MULYA DAN KESESUAIANNYA SEBAGAI BAHAN AJAR SASTRA DI SMA - Wijayanti, Tri Lutmasari; Sholeh, Khabib; Faizah, Umi; Santoso, Suryo Daru (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2025)
Abstract : Social critique is essential for evaluating the functioning of social systems within a community and can be communicated through various forms. Critical thinking is necessary to foster empathy toward one’s surroundings. However, social critique has yet to receive adequate attention in school curricula, despite educators' potential to use literature as a tool to develop students’ critical thinking skills. This study aims to describe the social critique within Adhitya Mulya's novel Sabar Tanpa Batas through qualitative descriptive research using content analysis. Data collection involved literature review techniques, observation, and note-taking. The findings reveal that the social critique in Sabar Tanpa Batas includes: (1) Poverty, which encompasses the challenges and costs of accessing education, low income levels, and difficulties in finding employment; (2) Crime, including cases of abuse; (3) Family disorganization, such as the absence of financial support from the head of the family and instances of child abuse; (4) The role of youth in society, including undervaluation of certain skills; (5) Population issues, such as the unaffordability of housing. Based on validity, relevance, and interviews with informants, the social critique in Sabar Tanpa Batas can serve as an alternative literary teaching material for twelfth-grade high school students.Keywords: social criticism, literature teaching material.